The PXDLS linear motif regulates circadian rhythmicity through protein–protein interactions. Issue 19 (26th September 2014) - Shalev, Moran; Aviram, Rona; Adamovich, Yaarit; Kraut-Cohen, Judith; Shamia, Tal; Ben-Dor, Shifra; Golik, Marina; Asher, Gad
Abstract: The circadian core clock circuitry relies on interlocked transcription-translation feedback loops that largely count on multiple protein interactions. The molecular mechanisms implicated in the assembly of these protein complexes are relatively unknown. Our bioinformatics analysis of short linear motifs, implicated in protein interactions, reveals an enrichment of the Pro-X-Asp-Leu-Ser (PXDLS) motif within circadian transcripts. We show that the PXDLS motif can bind to BMAL1/CLOCK and disrupt circadian oscillations in a cell-autonomous manner. Remarkably, the motif is evolutionary conserved in the core clock protein REV-ERBα, and additional proteins implicated in the clock's function (NRIP1, CBP). In this conjuncture, we uncover a novel cross talk between the two principal core clock feedback loops and show that BMAL/CLOCK and REV-ERBα interact and that the PXDLS motif of REV-ERBα participates in their binding. Furthermore, we demonstrate that the PXDLS motifs of NRIP1 and CBP are involved in circadian rhythmicity. Our findings suggest that the PXDLS motif plays an important role in circadian rhythmicity through regulation of protein interactions within the clock circuitry and that short linear motifs can be employed to modulate circadian oscillations.